2008
DOI: 10.1371/journal.pone.0002722
|View full text |Cite
|
Sign up to set email alerts
|

Global Regulation of Nucleotide Biosynthetic Genes by c-Myc

Abstract: BackgroundThe c-Myc transcription factor is a master regulator and integrates cell proliferation, cell growth and metabolism through activating thousands of target genes. Our identification of direct c-Myc target genes by chromatin immunoprecipitation (ChIP) coupled with pair-end ditag sequencing analysis (ChIP-PET) revealed that nucleotide metabolic genes are enriched among c-Myc targets, but the role of Myc in regulating nucleotide metabolic genes has not been comprehensively delineated.Methodology/Principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
219
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(244 citation statements)
references
References 51 publications
18
219
0
3
Order By: Relevance
“…Collectively, our findings suggest that individual genes encoding rate-limiting proteins involved in basic cell biological processes respond to the difference between physiological and supraphysiological MYC levels and that OmoMYC specifically inhibits tumor cell growth since it suppresses expression of this group of genes. A similar picture has emerged from studies of nucleotide biosynthesis genes: despite pervasive binding of MYC to promoters of nucleotide biosynthetic enzymes 46 , deregulation of a single rate-limiting enzyme, phosphoribosylpyrophosphate synthetase 2 (PRPS2), promotes the increased nucleotide biosynthesis of MYC-transformed cells 47 . A complete understanding of how to mimic OmoMYC´s efficacy with small molecule inhibitors will therefore require an analysis of its target genes in an in vivo setting.…”
Section: Discussionmentioning
confidence: 72%
“…Collectively, our findings suggest that individual genes encoding rate-limiting proteins involved in basic cell biological processes respond to the difference between physiological and supraphysiological MYC levels and that OmoMYC specifically inhibits tumor cell growth since it suppresses expression of this group of genes. A similar picture has emerged from studies of nucleotide biosynthesis genes: despite pervasive binding of MYC to promoters of nucleotide biosynthetic enzymes 46 , deregulation of a single rate-limiting enzyme, phosphoribosylpyrophosphate synthetase 2 (PRPS2), promotes the increased nucleotide biosynthesis of MYC-transformed cells 47 . A complete understanding of how to mimic OmoMYC´s efficacy with small molecule inhibitors will therefore require an analysis of its target genes in an in vivo setting.…”
Section: Discussionmentioning
confidence: 72%
“…Both c-Myc and E2F1 are important regulators of cell cycle, and it has been suggested that c-Myc metabolic gene targets are regulated in a cell-cycle-dependent way. Indeed, after induction of energy metabolism-and ribosomal biogenesis-related genes during the G 1 phase, c-Myc induces E2F1 expression as cells enter into the S phase, that together with c-Myc activates genes involved in nucleotides biosynthesis and DNA replication (Liu et al, 2008). There is no need to discuss the importance of Ras oncogenes in the control of cell proliferation and tumor development (Drosten et al, 2010).…”
Section: Metabolism Proliferation and Cancer V Fritz And L Fajasmentioning
confidence: 99%
“…All these results point to the enigmatic roles and underlying mechanisms for cMyc yet to be further elucidated under developmental or oncogenic circumstances. cMyc has been extensively documented to regulate glucose, glutamine and nucleotides metabolism [7,[40][41][42][43], nevertheless, it is unclear whether cMyc also controls the serine/glycine metabolism, especially under nutrient-deprived conditions.…”
Section: Introductionmentioning
confidence: 99%